Integrasi Etnik Tionghoa dengan Etnik Bali di Kuta 1968-2000 - Anggi Septiarana, Ni Made; Bagus Wirawan, A.A; Wirasmini Sidemen, Ida Ayu (Humanis, 2017)
This study describes the integration of Tionghoa ethnic with Balinese ethnic in Kuta 1968-2000, this research uses field research type, completed with archive research, interview and observation directly to Tionghoa ethnic and Balinese ethnic activities in Kuta. In this research, Tionghoa ethnic process is able to survive and integrated in Balinese ethnic structure in Kuta after the issuance of PP. No. 10 year 1959 is a socio-economic and cultural aspect. In the study find some form of socio-economic and cultural integration that occurred between ethnic Chinese with ethnic Balinese Hindu in Kuta.